ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PEKERJA MENGGUNAKAN ALAT PELINDUNG DIRI - Ratna Lestari; Agus Warseno (JURNAL KESEHATAN MERCUSUAR, 2021)
The implementation of occupational health and safety among the industrial circle and society in Indonesia is still relatively low, thus resulted in an occupational accident. Preventive attempts or anticipation for occupational accidents can be conducted by fostering habituation of order, discipline, and maintaining a healthy and safe environment through worker compliance to Personal Protective Equipment (PPE). The use of Personal Protective Equipment will safeguard the workers from potential hazards in the workplace. This research aims to find factors related to worker compliance in using Personal Protective Equipment in Madubaru Inc. Yogyakarta. This research is correlation research with the cross-sectional approach. The sample in this research are 86 workers, in steam boiler station and milling obtained using purposive sampling. Data collection is conducted through the Personal Protective Equipment compliance questionnaire. Additionally, data analysis is performed using a correlation analysis test with chi-square with a confidence level of 95 % (α= 0.05). The finding of this research showed that 76. 7 % of workers did not comply with the utilization of PPE. All variables were not related to the worker compliance in using PPE that is age (p-value 0. 942), education (p-value 0. 300), the length of employment (p-value 0. 077), employment status (p-value 0. 797), knowledge (p-value 0. 961), attitude (p-value 0. 780), motivation (p-value 0. 487), supervision (p-value 0.674), and PPE availability (p-value 0.222It can be concluded that individual characteristics, knowledge, attitude, motivation, supervision, and availibility had no significant correlation with PPE compliance in Madubaru Inc. Yogyakarta.